The Development and Validation of a Filipino Social Desirability Scale. - Cagasan, L.P. Jr
This paper is composed of two studies that describe the construction and validation of a Filipino Social Desirability (SD) Scale. Study 1 details the phases in developing the SD scale: item writing, item selection, and cross validation. In the item-selection phase, twelve of the twenty-six candidate items were selected based on a number of criteria. One is the correlation of items with self-criterion residuals, defined as the discrepancy between self-report scale scores and an objective criterion, in this case, peer-rating on the same scale. Residuals were generated from the five domain scores of the Mapa ng Loob. Other criteria were psychometric properties of the items and ratings of experts and target participants on the appropriateness of the items. On a sample with n = 157, the test-reliability of the scale was found to be .706. In the cross validation phase, SD scale scores (from 12 items) were found to be significantly correlated with self-peer discrepancies on Neuroticism, Agreeableness, and Conscientiousness. The scale reliability was computed at .731 (n = 162). In Study 2, convergent validity of the local SD scale was examined. Results showed that the Filipino Social Desirability Scale was significantly correlated with Paulhus? Balanced Inventory of Desirable Responding and the Marlowe-Crowne SD Scale.